Transactional client-server cache consistency alternatives and performance. - Franklin , Michael J. (ACM transactions on database systems.)
Client-server database systems based on a data shipping model can exploit client memory resources by caching copies of data items across transaction boundaries. Caching reduces the need to obtain data from servers or other sites on the network. In order to ensure that such caching does not result in the violation of transaction semantics, a transactional cache consistency maintenance algorithm is required. Many such algorithms have been proposed in the literature and, as all provide the same functionality, performance is a primary concern in choosing among them. In this article we present a taxonomy that describes the design space for transactional cache consistency maintenance algorithms and show how proposed algorithms relate to one another. We then investigate the performance of six of these algorithms, and use these results to examine the tradeoffs inherent in the design choices identified in the taxonomy. The results show that the interactions among dimensions of the design space impact performance in many ways, and that classifications of algorithms as simply ?pessimistic? or ?optimistic? do not accurately characterize the similarities and differences among the many possible cache consistency algorithms.